2009
DOI: 10.1111/j.1469-7610.2008.01929.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of parenting practices as a mediator of early childhood physical aggression

Abstract: There was support for the hypothesized model of the prevention of physical aggression during early childhood. Intervention benefits on parenting practices partially accounted for intervention effects on physical aggression in young high-risk children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 59 publications
3
45
0
1
Order By: Relevance
“…Overall, findings of long-term group differences on obesity, health behaviors and blood pressure reinforce earlier demonstrations of the broad range of benefits from behavioral family intervention for children with or at risk for behavior problems [30][31][32][33][34][35][56][57][58][59][60] and are consistent with theoretical models that implicate parenting in the promotion of healthy physical development. Reductions in BMI among overweight Australian children whose parents participated in a treatment program to improve parenting (eg, responsiveness) also provide support for this approach.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Overall, findings of long-term group differences on obesity, health behaviors and blood pressure reinforce earlier demonstrations of the broad range of benefits from behavioral family intervention for children with or at risk for behavior problems [30][31][32][33][34][35][56][57][58][59][60] and are consistent with theoretical models that implicate parenting in the promotion of healthy physical development. Reductions in BMI among overweight Australian children whose parents participated in a treatment program to improve parenting (eg, responsiveness) also provide support for this approach.…”
Section: Discussionsupporting
confidence: 69%
“…[30][31][32][33][34][35] We expected that study participants were also at risk for obesity and hypothesized that family intervention in early childhood would mitigate this risk, resulting in lower rates of obesity. The current study takes advantage of 2 RCTs with prospective follow-up studies of behavioral outcomes to examine intervention effects on obesity and related health behaviors as high-risk youth approach adolescence.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…Smit et al, 2008;Kaminski, Valle, Filene & Boyle, 2008) indicated that these interventions have demonstrated efficacy in preventing substance use and other child problem behaviors. These positive results have been reported in different settings (Aalborg et al, 2010;Letarte, Normandeau & Allard, 2010;Redmond et al, 2009;Henggeler & Schoenwald, 2011;Brook, McDonald & Yan, 2012;Donavan, Wood, Frayjo, Black & Surette, 2012), target groups (Mindel & Hoefer, 2006;Orte, Touza, Ballester & March, 2008;McDaniel, Braiden, Onyekwelu, Murphy & Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, & Matthys, 2012;Kumpfer, Whiteside, Greene & Allen, 2010), cultures (Skärstrand, Larsson & Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie & O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina & Ciairano, 2012) and addicted behaviours (Trudeau, Spoth, Randall & Azevedo, 2007;Zhong, et al, 2011;Donovan et al, 2012). …”
Section: Objeto Y Alcance De La Presente Revisión Bibliográficamentioning
confidence: 76%
“…Por ello, los componentes más importantes de estos programas incluyen la interacción positiva padres-hijos, enseñar a los padres a usar el "tiempo fuera", ofrecer reafirmación positiva, enseñar habilidades de comunicación y fijación de reglas. Las habilidades de resistencia social y a los coetáneos, el desarrollo de normas de conducta y buscar la compañía de coetáneos positivos, también se pueden abordar desde un programa universal basado en la familia para la prevención de las toxicodependencias (Lochman y Steenhoven, 2002 (Aalborg et al, 2010;Letarte, Normandeau y Allard, 2010;Redmond et al, 2009;Henggeler y Schoenwald, 2011;Brook, McDonald y Yan, 2012;Donavan, Wood, Frayjo, Black y Surette, 2012), grupos meta (Mindel y Hoefer, 2006;Orte, Touza, Ballester y March, 2008;McDaniel, Braiden, Onyekwelu, Murphy y Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, y Matthys, 2012;Kumpfer, Whiteside, Greene y Allen, 2010), culturas (Skärstrand, Larsson y Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie y O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina y Ciairano, 2012) y conductas adictivas (Trudeau, Spoth, Randall y Azevedo, 2007;Zhong et al, 2011;Donovan et al, 2012).…”
Section: Introductionunclassified